ANALISIS POTENSI PENERIMAAN RETRIBUSI PELAYANAN PARKIR DI TEPI JALAN UMUM KOTA BANJARMASIN - MUHAMMAD REZA RUSYADI; MUHAMMAD HANDRY IMANSYAH (PPJP Universitas Lambung Mangkurat, 2019)
The purpose of this study was to see the actual potential of revenue from the retribution of parkirng services on the edge of the public roads of Banjarmasin City in 2018. The type of research used is descriptive statistics, with a population of 208 parking retribution points in 5 sub-districts of Banjarmasin City and using the Slovin test to determine 22 samples. The data used is primary data obtained from field observations. The analysis techinque used is selecting sampling and standard deviation techniques. Selecting sampling by observasing for 10 minutes parking reception at busy and quiet hours on weekdays and weekends. While the standard deviation is used to see the upper and lower limits of potensial retribution for parking service on the edge of public roads.The results obtained in this study show that the target set is able to cross the lower standard deviation, which means that the performance of the local government, especially the transportation agency, is quite good, but the revenue from the on-street parking retribution can be improved. For the North Banjarmasin region it can be increased by 101%, then South Banjarmasin by 218%, then for the West Banjarmasin region by 26%, then for East Banjarmasin by 26% and the Central Banjarmasin area by 23%. Whereas for the the centra antasari market, it can be increased by 29%Keyword: Potential, selecting sampling, parking retribution.